Test of the Inhibitory Power of Virgin Coconut Oil on the Growth of Candida albicans - Christy N. Mintjelungan; Damajanty H.C. Pangemanan; Sherry Deiristi Sulangi (Sam Ratulangi University, 2024)
Treatment of oral candidiasis with the primary causative agent Candida albicans currently uses synthetic antifungal drugs which can cause various adverse side effects, for this reason an alternative is needed by using natural products, one of which can be using pure coconut oil (VCO) which is proven to contain medium chain fatty acids (MCFAs) and are useful as antifungals. This study aimed to determine the inhibitory power of VCO on the growth of the Candida albicans. The research used is laboratory experimental research, using a true experimental design with a post test only control group design. Inhibitory power testing can be done using the well method. Samples were divided into treatment groups with respective concentrations of 25%, 50%, 75%, 100%, positive control (Chlorhexidine gluconate 0.2%), and negative control (dimethyl sulfoxide). The normality test results show p > 0.05, which means the data was normally distributed. The One Way Anova test showed p < 0.05, which means there were differences in each treatment. In conclusion, VCO had a smaller inhibitory power than the positive control Chlorhexidine gluconate 0,2% against the growth of the Candida albicans. Keywords: Candida albicans; medium chain fatty acids; Virgin Coconut Oil